Pengaruh Kreativitas Guru terhadap Motivasi Belajar Siswa di SMP YPN Bojonggede Bogor - Marwati Ulfah; Eda Laelasari; Ismail Mustaqim (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2021)
The research was in the background by viewing the fact on the ground that many students are often bored and students tend to passively listen to the teacher's descriptions because the less attractive lesson material transmission and the lack of communication between teacher and student in the lesson, resulting in a lack of student's learning motivation. With that background, researchers are intrigued to examine whether the creativity of a teacher in Islam is affecting students' learning motivation. The research was conducted in Junior High School YPN Bojonggede Bogor. The population is 103 students while the sample is 35 students. The study implemented correlation methods with research instruments using angkets for the creativity of the islamic religious education teacher and student learning motivation. Data was analyzed using product moment correlation techniques. Research shows r calculated= 0.47 > r table= 0.344. Thus Ha is accepted and Ho rejected which means there is an influence in the creativity of teachers of Islam's education on students' learning motivation. So is the significance test with t test show t count 3.0590 > t table 2.0301. This means the influence of the creativity of the islamic religious education teacher on student learning motivation is a significant influence, while the contribution of the creativity of the islamic religious education teacher on the student's learning motivation is shown by KD (Coefficient of Determination) as 22.09%.